2020
DOI: 10.3390/toxins12050310
|View full text |Cite
|
Sign up to set email alerts
|

The First Proteomic Study of Nostoc sp. PCC 7120 Exposed to Cyanotoxin BMAA under Nitrogen Starvation

Abstract: The oldest prokaryotic photoautotrophic organisms, cyanobacteria, produce many different metabolites. Among them is the water-soluble neurotoxic non-protein amino acid beta-N-methylamino-L-alanine (BMAA), whose biological functions in cyanobacterial metabolism are of fundamental scientific and practical interest. An early BMAA inhibitory effect on nitrogen fixation and heterocyst differentiation was shown in strains of diazotrophic cyanobacteria Nostoc sp. PCC 7120, Nostoc punctiforme PCC 73102 (ATCC 29133), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(78 citation statements)
references
References 84 publications
(145 reference statements)
11
66
1
Order By: Relevance
“…In order to test BMAA effect on Nostoc under nitrogen-replete conditions, cyanobacterium was grown in three independent biological replicates in sodium nitrate containing BG11N medium for 48 h in two experimental settings: (1) control samples consisted of cells grown without the BMAA treatment and (2) the treated samples consisted of cells grown with addition of an aqueous solution of BMAA (20 µM), as it was performed earlier [ 22 , 23 ]. The analysis of cyanobacteria samples by using LC-MS/MS methods resulted in the identification of 1567 different proteins of Nostoc ( Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to test BMAA effect on Nostoc under nitrogen-replete conditions, cyanobacterium was grown in three independent biological replicates in sodium nitrate containing BG11N medium for 48 h in two experimental settings: (1) control samples consisted of cells grown without the BMAA treatment and (2) the treated samples consisted of cells grown with addition of an aqueous solution of BMAA (20 µM), as it was performed earlier [ 22 , 23 ]. The analysis of cyanobacteria samples by using LC-MS/MS methods resulted in the identification of 1567 different proteins of Nostoc ( Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The PII signal-transduction protein plays a key role in the control of various nitrogen-related transporters, enzymes and transcription factors ( Figure 1 and Figure 2 ) [ 28 ]. In our previous proteomic study [ 23 ], we found that BMAA downregulated the PII protein in nitrogen-starved Nostoc cells that should have formed heterocysts, however, this process is repressed by BMAA [ 21 ]. Remarkably, in nitrogen starvation conditions, the addition of BMAA alters the expression of the nitrate transporter nrtA ( alr0608 ) [ 23 ], a partner of PII protein [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations